INSTITUTIONALIZATION OF THAYYIB AS A FOOD REGULATORY INSTRUMENT: A MAQASID AL-SHARI’AH FRAMEWORK FOR CONSUMER PROTECTION - Sofwan Hadikusuma; Dwi Nora Kharisma (Referensi Islamika: Jurnal Studi Islam, 2026)
This study examines a structural paradox in Indonesia’s food system in which the halal dimension has been fully institutionalized to ensure the legality of consumption, while the thayyib dimension, which concerning the quality of consumption, remains underdeveloped, despite both being consistently enjoined together in Islamic dietary prescriptions. The study aims to construct a normative justification for the institutionalization of thayyib as a regulatory instrument that operates alongside halal within Indonesia’s food governance system. The study employs a normative-conceptual approach, drawing on contemporary maqāṣid al-sharīʿah and the diyānatan–qaḍāʼan distinction in the fiqh tradition. These frameworks are used to construct a dual-legitimacy model that integrates religious obligation (diyānatan) with state-enforceable legal obligation (qaḍāʼan). The study finds that the institutionalization of thayyib can be normatively justified through a model grounded in three cumulative conditions: the presence of public interest, the insufficiency of voluntary moral compliance, and the availability of institutional enforcement capacity. This model also provides a generalized evaluative framework for assessing the legitimacy of state intervention in other Islamic norms that currently operate primarily at the moral level. This study is limited to a normative-conceptual framework and does not develop a technical regulatory design or empirically test consumer responses. The applicability of the model beyond the Indonesian context requires further investigation. This study contributes by operationalizing the diyānatan–qaḍāʼan distinction as a public policy legitimacy framework and extending maqāṣid al-sharīʿah into the domain of food regulation. It advances a dual-legitimacy model and proposes a thayyib label placed alongside the halal label on food packaging as a concrete policy instrument.